Optimizing Safety of Iliac Bone Harvest Using an Acumed Drill: A Simulated Radiographic Study of 100 Patients. (November 2017) - Stranix, John T.; Cuzzone, Daniel; Ly, Catherine; Topilow, Nicole; Runyan, Christopher M.; Ream, Justin; Flores, Roberto L.
Objective: To determine the potential risk of visceral injury during Acumed drill iliac crest cancellous bone graft harvest. Design: Radiographic iliac crest anatomic analysis with simulated drill course to measure cancellous bone available for harvest and proximity of vulnerable pelvic structures. Setting: Single institution, tertiary care university hospital. Patients and Participants: One hundred pelvic computed tomography scans performed on children 8 to 12 years old without traumatic or neoplastic pathology. Interventions: Radiographic simulation of Acumed drill course within iliac bone. Main Outcome Measures: (1) Potential for pelvic visceral injury. (2) Volume of cancellous bone safely available for harvest. Results: Superior and medial cortical thickness at the reference point remained stable across age groups; however, lateral cortical thickness increased with age (3.13 to 3.74 mm, P < .001). Cancellous bone width increased with age at all depths measured ( P < .001). Through radiographic simulation, the drill could reach the bowel in 4% of cases and only through gross deviation (>30°) from the plane of the ilium. There were no cases of simulated bowel perforation within 3 cm of the reference point. The maximum cancellous volume safely harvested increased with age: 24 cc in 8-year-olds to 36 cc in 12-year-olds ( P < .001). Conclusions: Acumed assisted iliac crest bone graft harvest is a safe technique in which substantial amount of cancellous bone can be obtained. The low risk of bowel perforation can be further minimized by limiting the depth of drill bit penetration to less than 3 cm.